Knowledge Management: Adoptions And Influence On The Implementation Of Competency Apprenticeship Smes “Style” In Makassar - Ria Mardiana Yusuf; Nurdjanah Hamid; Andi Ratna Sari Dewi (Cita konsultindo, 2023)
Economic development of a nation is strongly influenced by the development of creative enterprises, namely Small and Medium Enterprises (SMEs). SMEs are considerably concerned to be the foundation of a country against the poverty issues. Some studies reveal the contribution of SMEs contribute up to 60.34 percent to a country's GDP. However, SMEs experience a variety of basic problems, among others, on knowledge adoption applied in SME-organizations as well as apprenticeship for the competency improvements of SMEs. Adaptability and adoption ability of knowledge in SMEs is one of the emerging issues (Kusumawijaya and Astuti, 2012; Ley T. et al., 2005). The study aims to analyse the knowledge management adoption; consist of leadership, mutual understanding, system adoption, and learning culture; and its influence on apprenticeship competency of culinary SMEs in Makassar, both as a whole and partially. Employing a descriptive quantitative research design to 124 employees of culinary SMEs in Makassar, the results indicate the whole determinants can show a positive effect interactively to the competency apprenticeship of SMEs in Makassar. Contrary, only learning culture demonstrates a positive partial effect on the competency apprenticeship of employee